Politics of Randomness - Gil S. Epstein; Shmuel Nitzan (Center for Economic Studies and ifo Institute (CESifo), 2002)
The main drawback of the public-policy contest is that the notion of contest success function, a crucial component of the contest model, does not have micro-foundations and, therefore, the random behavior of the government seems ad-hoc. In the present paper we propose a partial micro-foundation for the public-policy contest. The possible rationalization of random government behavior is illustrated in the case of the all-pay auction and Tullock's lottery logit functions. We also clarify how stake asymmetry, lobbying-skill asymmetry and return to lobbying effort determine the relative desirability, from the government's point of view, of these CSFs
Keywords: 330; interest groups; policy makers; lobbying; public-policy contests; contest success function; rationalization of random government's behavior